ASUHAN KEBIDANAN PEMBERIAN SARI KURMA UNTUK MENINGKATKAN KADAR HEMOGLOBIN IBU HAMIL DENGAN ANEMIA DI PUSKESMAS TANJUNG BALAI KARIMUN - Maryati; Sarmauli Franshisca Sihombing (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
According to WHO, the global prevalence of anemia in pregnant women worldwide is 41.8%. The main cause of anemia in pregnancy is iron deficiency, followed by folate deficiency. One way to overcome anemia in pregnancy is by consuming iron foodstuffs, including dates. The purpose of this study was to provide integrated midwifery care for pregnant women with mild anemia by giving date juice to increase hemoglobin levels. Midwifery care uses a midwifery management approach. This type of research uses case study qualitative data. Midwifery care was carried out at the Tanjung Balai Health Center with subjects pregnant women at 32 weeks of gestation with mild anemia. The research instrument uses a case study format and observation sheets. Data collection techniques use primary data through anamnesis, physical examination, interviews and observation. Evaluation of the care provided related to giving date palm juice 3 times a day can help increase HB levels. For health workers, it is hoped that they can improve the quality of midwifery services through a management approach to midwifery care for the prevention of mild anemia with date juice.